Hubungan Penggunaan Kontrasepsi Hormonal Terhadap Kejadian Hipertensi Pada Wanita Usia Subur di Puskesmas Teluk Dalam Nias Selatan Tahun 2023 - Ervira Seprina; Adelina Sembiring; Nur Azizah (Pusat Riset dan Inovasi Nasional, 2024)
Hypertension Hypertension is still a big problem and challenge in Indonesia, because it is still often found in primary health services and the prevalence rate is still high and has increased compared to previous years. The side effects that occur if you experience an increase in blood pressure that lasts for a long time are damage to the kidneys (kidney failure), heart (coronary heart disease) and brain, which can cause a stroke if not detected early and given adequate treatment. And it can also cause death. The aim of the research is to determine the relationship between the use of hormonal contraception and the incidence of hypertension in women of childbearing age at the Teluk Dalam South Nias Community Health Center in 2023.The type of research carried out was Descriptive Analytical with a cross sectional approach, the sample in this study was 102 people using Total Sampling. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square The results of the cross-tabulation research on the use of hormonal contraception at the Teluk Dalam South Nias Community Health Center in 2023, the majority used injectable contraceptives, 65 respondents (63.7%), the blood pressure at the Teluk Dalam Health Center, South Nias in 2023, the majority was normal, 52 respondents (51.0 %), there is a relationship between the use of hormonal contraception and the incidence of hypertension in women of childbearing age (WUS) at Teluk Dalam South Nias Community Health Center in 2023 with a value of p = 0.000. So Ho is rejected and Ha is accepted, which means that there is a relationship between the use of hormonal contraception and the incidence of hypertension in women of childbearing age at Teluk Dalam Health Center, South Nias. Suggestions for future researchers are that they can carry out further research by developing other variables to get better results.